A Double-Blind, Placebo-Controlled Study of Adjunctive Topiramate in Adolescents With Co-Occurring Bipolar and Cannabis Use Disorders - Farrow, Jenni E.; DelBello, Melissa P.; Patino, Luis R.; Blom, Thomas J.; Welge, Jeffrey A. (JAACAP open, 2024)
To evaluate the efficacy of adjunctive topiramate (TPM) for the treatment of cannabis use disorder in adolescents with bipolar I disorder. We conducted a 16-week, double-blind, randomized, placebo-controlled investigation of quetiapine plus TPM (median dose = 208 mg) vs quetiapine plus placebo in adolescents with bipolar I and cannabis use disorder. All subjects participated in a Motivational Interview and Compliance Enhancement Therapy. The primary outcome measure was change in weekly cannabis use over a 16-week treatment period using the Timeline Followback. The secondary outcome measure was the baseline-to-endpoint total score change in the Young Mania Rating Scale (YMRS). A total of 75 participants completed at least 1 post-baseline assessment (TPM = 38, placebo = 37). There was a significant time-by-treatment effect over the 16-week treatment period, with baseline-adjusted treatment differences in favor of the TPM group over time (p < .001). Although there was no difference in baseline-to-endpoint YMRS total score change between groups (p = .342), there was as significant decline in YMRS total score within both groups (p < .0001). There was a significant positive effect for alcohol use (p < .001) and nicotine use (p = .033) in the TPM group. More participants in the TPM group experienced appetite decrease (p = .032) and excitement (p = .025). Participants in the placebo group experienced greater weight gain (p = .010). Treatment with TPM adjunctive to quetiapine and a Motivational Interview and Compliance Enhancement Therapy is associated with a greater decrease in cannabis use and less weight gain. TPM is a well-tolerated and efficacious treatment for cannabis use disorder in adolescents with bipolar I disorder. Cannabis is the most commonly misused drug in adolescents with bipolar disorder, and there is limited prior research supporting the addition of topiramate to motivational enhancement for the treatment of cannabis use disorder. In this study, 75 adolescents and young adults, aged 12-21, with bipolar I disorder participated in a 16-week, double-blind, randomized, placebo-controlled trial of quetiapine plus topiramate versus quetiapine plus placebo treatment for cannabis use disorder. All subjects participated in a Motivational Interview and Compliance Enhancement Therapy. The group receiving topiramate had a greater decrease in the use of cannabis, alcohol, and nicotine, as well as less weight gain. These results suggest that adjunctive topiramate to quetiapine and motivational interview may be helpful in the treatment of cannabis use disorder in adolescents and young adults with bipolar 1 disorder. Efficacy Study of Quetiapine Plus Topiramate for Reducing Cannabis Consumption and Bipolar Mania; https://clinicaltrials.gov/; NCT00393978. We worked to ensure sex and gender balance in the recruitment of human participants. We worked to ensure race, ethnic, and/or other types of diversity in the recruitment of human participants. We worked to ensure that the study questionnaires were prepared in an inclusive way. One or more of the authors of this paper self-identifies as a member of one or more historically underrepresented racial and/or ethnic groups in science.